The efficacy of regorafenib monotherapy as the third-and later-line treatment for metastatic colorectal cancer: a retrospective study - An Tianqi; Song Lijie; Zong Hong; Zhao Ruihua (结直肠肛门外科)
[Objectives] To investigate the efficacy and safety of regorafenib monotherapy as the third-and later-line treatment for metastatic colorectal cancer. [Methods] This was a retrospective analysis of 32 patients with metastatic colorectal cancer receiving regorafenib monotherapy as the third-and later-line treatment between November 13, 2018, and February 28, 2022, at the First Affiliated Hospital of Zhengzhou University. Primary endpoints included progression-free survival (PFS) and overall survival (OS). Secondary endpoints included objective response rate (ORR), disease control rate (DCR), and adverse events. [Results] Of the 32 patients, none (0%, 0/32) achieved complete response, 1 (3.1%, 1/32) achieved partial response, 20 (62.5%, 20/32) achieved stable disease, and 11 (34.4%, 11/32) achieved progressive disease. ORR was 3.1%. DCR was 65.6%. Median PFS and OS were 3.7 months (95% confidence interval: 2.4~8.1) and 17.4 months (95% CI: 8.9~infinite), respectively. DCR and PFS were both significantly higher in patients who had not previously used bevacizumab and received regorafenib monotherapy as the third-and later-line treatment were better than those who had used bevacizumab (P=0.029 and P=0.041, respectively). Independent risk factors for OS were primary lesions that have not been resected (P=0.022) and more than three metastasized lesions (P=0.033). The common adverse events were alanine aminotransferase/aspartate aminotransferase elevation (9/32, 28.1%), hand-foot syndrome (8/32, 25%), and alkaline phosphatase elevation (7/32, 21.9%). Seven patients had adverse events of grades Ⅲ to Ⅳ. No patients had life-threatening or uncontrollable adverse events. [Conclusion] Regorafenib monotherapy as the third-and later-line treatment shows acceptable efficacy and manageable safety for metastatic colorectal cancer.